2009
DOI: 10.4021/jocmr2009.12.1279
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transfusion Practices in Total Joint Arthroplasties in Jamaica

Abstract: BackgroundMajor blood loss usually occurs in both hip and knee arthroplasty, frequently leading to the need for blood transfusion. This study was performed to determine blood transfusion rates and analyze the factors which affected the need for blood transfusion in patients who underwent primary unilateral total knee and hip arthroplasties at the University Hospital of the West Indies, Jamaica.MethodsA prospective study of 118 patients who underwent unilateral total knee and total hip arthroplasties between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In addition to this, the absence of a blood management protocol has resulted in a wide variability of transfusion practices following joint replacement [ 16 ]. The only study from the Caribbean that attempted to address this issue reported a 63% blood transfusion rate following primary arthroplasty [ 17 ]. Limited blood availability together with high transfusion rates has prompted a search for more innovative and cost-effective methods to reduce the need for blood during arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, the absence of a blood management protocol has resulted in a wide variability of transfusion practices following joint replacement [ 16 ]. The only study from the Caribbean that attempted to address this issue reported a 63% blood transfusion rate following primary arthroplasty [ 17 ]. Limited blood availability together with high transfusion rates has prompted a search for more innovative and cost-effective methods to reduce the need for blood during arthroplasty.…”
Section: Discussionmentioning
confidence: 99%